2015
DOI: 10.1089/gtmb.2014.0177
|View full text |Cite
|
Sign up to set email alerts
|

RFC-180G>A Polymorphism in Case-Mother/Control-Mother Dyads Is Associated with Risk of Nephroblastoma and Neuroblastoma

Abstract: Aim: Embryonic tumors are associated with an interruption during normal organ development; they may be related to disturbances in the folate pathway involved in DNA synthesis, methylation, and repair. Prenatal supplementation with folic acid is associated with a decreased risk of neuroblastoma, brain tumors, retinoblastoma, and nephroblastoma. The aim of this study was to investigate the association between MTHFR rs1801133 (C677T) and RFC-1 rs1051266 (G80A) genotypes with the risk of developing nephroblastoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…MTHFR 667C>T (rs1801133), one of the most highly studied variants with known functional effects on one-carbon metabolism, [3739] had a null offspring association (RR: 0.99, 95% CI: 0.84–1.19) and a weak maternal association (RR: 1.16, 95% CI: 0.97–1.38). Two previous studies of candidate SNPs from folate-related genes identified SLC19A1 80G>A (rs1051266) as positively associated with neuroblastoma in Brazil [40, 41]. Montalvão-de-Azevedo et al found maternal carriers of the G had 3 times the risk of offspring with neuroblastoma and offspring carriers had approximately 2.5 times the risk, which was replicated by de Miranda et al [40, 41].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…MTHFR 667C>T (rs1801133), one of the most highly studied variants with known functional effects on one-carbon metabolism, [3739] had a null offspring association (RR: 0.99, 95% CI: 0.84–1.19) and a weak maternal association (RR: 1.16, 95% CI: 0.97–1.38). Two previous studies of candidate SNPs from folate-related genes identified SLC19A1 80G>A (rs1051266) as positively associated with neuroblastoma in Brazil [40, 41]. Montalvão-de-Azevedo et al found maternal carriers of the G had 3 times the risk of offspring with neuroblastoma and offspring carriers had approximately 2.5 times the risk, which was replicated by de Miranda et al [40, 41].…”
Section: Discussionmentioning
confidence: 84%
“…Two previous studies of candidate SNPs from folate-related genes identified SLC19A1 80G>A (rs1051266) as positively associated with neuroblastoma in Brazil [40, 41]. Montalvão-de-Azevedo et al found maternal carriers of the G had 3 times the risk of offspring with neuroblastoma and offspring carriers had approximately 2.5 times the risk, which was replicated by de Miranda et al [40, 41]. In NENA, we found no association (Maternal RR: 1.12, 95% CI: 0.96–1.32; offspring log-additive RR: 0.94, 95% CI: 0.79–1.11).…”
Section: Discussionmentioning
confidence: 99%
“…Folate pathway participates in DNA synthesis, methylation, and repair. Prenatal intake of folic acid is associated with a decrease in the risk of childhood malignancies including neuroblastoma and nephroblastoma [ 30 ]. A G80A (rs1051266) polymorphism in the RFC1 gene, encoding a folate transporter in the cell membrane, was found to associate with increased susceptibility to nephroblastoma and neuroblastoma in Brazilian children [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in key BER genes may modify BER kinetics and capacity, which further alter cellular DNA repair ability and cause cell dysfunction, mutagenesis, and ultimately carcinogenesis [ 40 , 43 ]. Thus far, no evidence of linkage between BER SNPs and Wilms tumor has been reported; however, a few studies suggest the implication of DNA repair genes in Wilms tumor [ 28 , 30 ]. Due to their universal implications in carcinogenesis, we systematically investigated the association between SNPs within the BER pathway and Wilms tumor risk.…”
Section: Introductionmentioning
confidence: 99%
“…Chango et al 36 indicated that individuals carrying AA genotype had higher plasma folate levels than those carrying GG genotype. Recently, increasing evidences have highlighted the importance of RFC1 G80A polymorphism in the pathogenesis of malignance 37 - 39 .…”
Section: Discussionmentioning
confidence: 99%